(untitled) (Semiárida, 2020)
Fire affects not only the vegetation but also the seedbank, the main propagule reservoir of Piptochaetium napostaense. Despite being a well-known species, there is little information of the effect of fire temperatures on the germination and emergence of P. napostaense seeds. In this study, we evaluated the germination and emergence of P. napostaense in response to temperatures and exposure times similar to those observed during a fire. Seeds of P. napostaense were exposed to different treatments that resulted from the combination of six temperature levels (20°C, 70°C, 90°C, 120°C, 140°C and 170°C) and three exposure times (5, 10 and 20 minutes). Results showed that moderate temperaturas (70°C, 90°C) stimulated the germination of P. napostaense and the combination of high temperatures and prolonged exposure times reduced seed viability, and affected seedlings emergence and biomass. Results indicate that germination success of P. napostaense seeds depends on both temperature and exposure time.